The salafiyah pesantren movement in Banten: Resistance and negotiation for institutional recognition - Ahmad, Ikhsan; Haryanti, Erni (UIN Sunan Gunung Djati Bandung, 2025)
This article analyzes the dynamics of the socio-religious movement of the Salafiyah Islamic Boarding School (Majelis Pesantren Salafiyah–MPS) in Banten in fighting for institutional recognition. Using the perspective of resource mobilization theory and framing analysis, this research explores the forms of resistance and negotiation carried out by MPS in response to marginalization by government policy. Research findings show that MPS mobilizes cultural resources based on religious values and the identity of Salafiyah Islamic boarding schools as a strategy to fight against discrimination in educational policies. Through the formation of formal organizations, collective action, and policy advocacy, MPS succeeded in influencing the birth of Regional Regulation No. 7 of 2012 concerning the Implementation of Education in Banten, which includes Salafiyah Islamic boarding schools within the framework of recognized educational institutions. This research contributes to an understanding of how Islamic boarding school-based religious social movements strive for institutional recognition through a combination of cultural resistance and political negotiation strategies.